Microbiomic Analysis of Bacteria Associated with Rock Tripe Lichens in Continental and Maritime Antarctic Regions - Zichen He; Takeshi Naganuma; Ryosuke Nakai; Satoshi Imura; Megumu Tsujimoto; Peter Convey (Journal of Fungi, 2022)
Increased research attention is being given to bacterial diversity associated with lichens. Rock tripe lichens (Umbilicariaceae) were collected from two distinct Antarctic biological regions, the continental region near the Japanese Antarctic station (Syowa Station) and the maritime Antarctic South Orkney Islands (Signy Island), in order to compare their bacterial floras and potential metabolism. Bulk DNA extracted from the lichen samples was used to amplify the 18S rRNA gene and the V3-V4 region of the 16S rRNA gene, whose amplicons were Sanger- and MiSeq-sequenced, respectively. The fungal and algal partners represented members of the ascomycete genus Umbilicaria and the green algal genus Trebouxia, based on 18S rRNA gene sequences. The V3-V4 sequences were grouped into operational taxonomic units (OTUs), which were assigned to eight bacterial phyla, Acidobacteriota, Actinomyceota, Armatimonadota, Bacteroidota, Cyanobacteria, Deinococcota, Pseudomonadota and the candidate phylum Saccharibacteria (also known as TM7), commonly present in all samples. The OTU floras of the two biological regions were clearly distinct, with regional biomarker genera, such as Mucilaginibacter and Gluconacetobacter, respectively. The OTU-based metabolism analysis predicted higher membrane transport activities in the maritime Antarctic OTUs, probably influenced by the sampling area’s warmer maritime climatic setting.